Fermi liquid properties of ³He –⁴He mixtures - Schörkhuber, K.; Krotscheck, E.; Paaso, J.; Saarela, M.; Zillich, R. (Condensed Matter Physics, 1999)
We calculate microscopically the properties of ³He impurity atoms in ³He –⁴He mixtures, including the spectrum of a single particle and the Fermi–
Liquid interaction between ³He atoms. From these, we determine the pressure and concentration dependence of the effective mass and the magnetic
susceptibility. The long wavelength limit of the single–particle spectrum deﬁnes the hydrodynamic effective mass. When k >= 1.7A⁻¹ the motion of the
impurity is damped due to the decay into a roton and a low energy impurity
mode. The calculations of the Fermi–Liquid interaction are based on correlated basis functions (CBF) perturbation theory; the relevant matrix elements are determined by the Fermi hypernetted–chain summation method.
Our theoretical effective masses agree well with recent measurements [1,2]
but our analysis suggests a new extrapolation to the zero-concentration
limit. With that effective mass we also ﬁnd a good agreement with the measured [3] Landau parameter Fa₀. Проведено мікроскопічне дослідження властивостей домішкових
атомів ³He у сумішах ³He –⁴He, зокрема, розраховано одночастинковий спектр та Фермі рідинну взаємодію для атомів ³He. На цій основі
знайдені залежності ефективної маси і магнітної сприйнятливості від
тиску і концентрації. Гідродинамічна ефективна маса визначається з
довгохвильової границі одночастинкового спектру. Для k >= 1.7 A⁻¹
рух домішки в силу розпаду на ротон та низькоенергетичне домішкове збудження є утруднений. Розрахунки Фермі рідинної взаємодії базувалися на теорії збурень з корельованими базисними функціями;
відповідні матричні елементи розраховувалися методом ферміонного гіперланцюжкового сумування. Теоретично отримані ефективні
маси добре узгоджуються з недавніми вимірюваннями [1,2], водночас проведений аналіз дозволив запропонувати нову екстраполяційну формулу для границі нульової концентрації. При цьому знайдено
також добре узгодження з параметром Ландау Fa₀, виміряним в [3].